Population-based cancer survival in the Golestan province in the northeastern part of Iran 2007–2012. (April 2022) - Nemati, Saeed; Saeedi, Elnaz; Roshandel, Gholamreza; Nahvijou, Azin; Badakhshan, Abbas; Akbari, Mahnaz; Sedaghat, Seyed Mehdi; Hasanpour-Heidari, Susan; Hosseinpour, Reza; Salamat, Faezeh; Lotfi, Fereshteh; Khosravi, Ardeshir; et al.
Abstract: Objective: We studied 5-year relative survival (RS) for 14 leading cancer sites in the population-based cancer registry (PBCR) of Golestan province in the northeastern part of Iran. Methodology: We followed patients diagnosed in 2007–2012 through data linkage with different databases, including the national causes of death registry and vital statistics office. We also followed the remaining patients through active contact. We used relative survival (RS) analysis to estimate 5-year age-standardized net survival for each cancer site. Multiple Imputation (MI) method was performed to obtain vital status for loss to follow-up (LTFU) cases. Results: We followed 6910 cancer patients from Golestan PBCR. However, 2162 patients were loss to follow-up. We found a higher RS in women (29.5%, 95% CI, 27.5, 31.7) than men (21.0%, 95% CI, 19.5, 22.5). The highest RS was observed for breast cancer in women (RS=49.8%, 95% CI, 42.2, 56.9) and colon cancer in men (RS=37.9%, 95% CI, 31.2, 44.6). Pancreatic cancer had the lowest RS both in men (RS= 8.7%, 95% CI, 4.1, 13.5) and women (RS= 7.9%, 95% CI, 5.0, 10.8) Conclusion: Although the 5-year cancer survival rates were relatively low in the Golestan province, there were distinct variations by cancer site. Further studies are required to evaluate the survival trends in Golestan province over time and compare them with the rates in the neighboring provinces and other countries in the region. Graphical Abstract: ga1 Highlights: This study is one of the most comprehensive attempts to estimate population-based cancer survival in the EMRO Region. Cancer survival in Golestan province was pretty low. The overall 5-year net survival was 25% in Golestan province. The highest 5-year net survival was in breast, colon, melanoma, leukemia, and rectum cancers.